Implementation of Fines for Traffic Violations at Rokan Hilir Police Department - Fajar Fisheri Nasution; Risdalina Risdalina; Indra Kumalasari M (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Sexual harassment cases are a serious problem that has an impact on various aspects of the victim's life, both physical and psychological. In Indonesia, the handling of this case is regulated by positive law which aims to provide legal protection for victims and fair sanctions for perpetrators. However, there are still various challenges in its implementation, such as unclear definitions and lack of comprehensive legal protection. This study aims to analyze the regulation of sexual harassment crimes from a positive legal perspective in Indonesia. This research uses a normative juridical method, which is a literature study that examines secondary legal materials such as laws, journals, and related literature. The results show that although there are several regulations regulating the crime of sexual harassment, there are still shortcomings in terms of clear definitions and comprehensive protection for victims. In addition, consistent application of the law and increasing legal awareness in the community are also challenges that need to be overcome. The implications of this study show the importance of revising and improving existing regulations as well as the need for a more holistic approach in handling sexual harassment cases. This research is expected to contribute to the development of more effective and fair legal policies in protecting the rights of victims of sexual harassment.